The Effect of Economic Growth on The Human Development Index in Indonesia - Asmara, Galuh Jati; Asmara, Gea Dwi; Saleh, Rahmat (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to test and analyze the effect of economic growth on the Human Development Index in 34 provinces in Indonesia. This research uses quantitative data methods. The independent variable used in this study is economic growth with control variables, namely poverty and population. The dependent variable used is the Human Development Index. The data type used is panel data, a combination of time series and cross-section. Time series data was obtained from 2015-2020, and cross-section data was obtained from 34 provinces in Indonesia. The data used is secondary data sourced from the Central Statistics Agency (BPS) report, especially from 2015 to 2020. Hypothesis testing in this study uses multiple linear regression with the Chow test, Hausman test, t-test, f-test, and coefficient of determination test. The results show that economic growth had no significant effect on the Human Development Index in Indonesia in 2015-2020, Ceteris Paribus. The control variables of poverty and population influence the Human Development Index. The poverty control variable has a significant negative effect, and the population control variable has a significant positive impact. This study contributes new empirical evidence to fill gaps and address inconsistencies in the existing literature on the relationship between economic growth and human development.